1993
DOI: 10.1063/1.353862
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering from PbTiO3 thin films prepared on silicon substrates by radio frequency sputtering and thermal treatment

Abstract: Articles you may be interested inCrystallization of Pb(Zr,Ti)O3 films prepared by radio frequency magnetron sputtering with a stoichiometric oxide target J. Vac. Sci. Technol. A 13, 2214 (1995); 10.1116/1.579545 Effects of surface structures of MgO(100) single crystal substrates on ferroelectric PbTiO3 thin films grown by radio frequency sputtering J. Vac. Sci. Technol. A 13, 95 (1995); 10.1116/1.579392Raman scattering study of lead zirconate titanate thin films prepared on silicon substrates by radio frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 35 publications
10
55
1
Order By: Relevance
“…The obtained temperature dependences of the soft mode frequencies and the damping (Figs. 1 and 2) (the damping is related to the width of the half-maximum for the Raman scattering lines) could explain the experimental results of Raman scattering from ferroelectric thin films [14,16,17]: a) the Raman frequencies for the thin film remarkabely shift to low frequencies compared with those for the bulk; b) the Raman lines of the thin film are broaded in comparison with those for the bulk; c) the line shapes of the film become broad as the temperature approaches T c .…”
Section: Numerical Results and Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The obtained temperature dependences of the soft mode frequencies and the damping (Figs. 1 and 2) (the damping is related to the width of the half-maximum for the Raman scattering lines) could explain the experimental results of Raman scattering from ferroelectric thin films [14,16,17]: a) the Raman frequencies for the thin film remarkabely shift to low frequencies compared with those for the bulk; b) the Raman lines of the thin film are broaded in comparison with those for the bulk; c) the line shapes of the film become broad as the temperature approaches T c .…”
Section: Numerical Results and Discussionmentioning
confidence: 68%
“…Recently, several research groups carried out Raman scattering studies to characterize the ferroelectric thin films and showed that all transverse optical (TO) phonons tended to depart from the corresponding positions of the bulk single crystal, implying that differences might exist between thin films and bulk single crystals [13][14][15][16][17][18]. Using Raman spectroscopy the temperature dependence of the phonon modes for thin ferroelectric films of PbTiO 3 is discussed by Taguchi et al [16] and Fu et al [17]. It was shown that in comparison with the single crystal spectra, the Raman frequencies for the thin film remarkably shift to low frequencies and that the Raman lines are broad.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Raman tensor for the tetragonal C 4v point group, only E(TO) modes are allowed in x zy x geometry and only A 1 (TO) modes appear in x zz x geometry. 37,38 The absence of any LO component of phonon modes in the 64 nm film spectra suggested an a-axis preferred orientation of the film, which was supported by the x-ray analysis.…”
Section: Thickness Effect In Pbtio 3 Thin Filmsmentioning
confidence: 54%
“…Similar observations were made for the sol-gel-processed 13 and r.f.-sputtered PT thin films. 28 The tetragonal-to-cubic transition temperature observed for each thickness is displayed in Fig. 10 along with the stress variation for all of the films.…”
Section: Raman Spectra At Room Temperaturementioning
confidence: 99%